RELIGION, EDUCATION, AND SPORTS: INTERNALIZATION OF ISLAMIC EDUCATION VALUES IN MAHATMA SPORTS - Saefulloh, Ahmad; Razali, Razali; Famularsih, Sari (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2019)
This article analyzes the need to internalize the values of Islamic education in sports. One of the sports that promotes Islamic values is Mahatma. Facts on the ground show that sports that develop in the midst of society today do not prioritize spiritual health only prioritizing physical health alone, while spiritual health also needs attention. So that this discussion is well directed, the authors focus the problem of discussion on how to internalize the values of Islamic education in Mahatma sports. The study was conducted at the Ministry of Religion in Padang, located at Jl. Duku No.5 Ujung Gurun, Padang Barat District Padang West Sumatra. The purpose of this study is to look at the efforts of sports participants in internalizing the value of Islamic education in every sports movement, it is necessary to have a detailed assessment of the stages of inculcation. This research is a descriptive qualitative research that is describing and interpreting objects as they are and analyzing them using scientific methods. Data collection by observation, direct interviews and documentation. The technique used in data analysis is data display, data reduction and conclusions carried out with snowballsampling techniques. The data validity technique uses source triangulation. The results showed that the internalization of Islamic education values for Mahatma sports members was through the establishment of rules of dress, ablution, reciting Istighfar, Al-Fatiah, praying, breathing, remembrance, blessing, friendly smile and the emergence of mutual forgiveness. Through internalization, the impact resulting from Mahatma's sport on health is not only physical health, it also increases gratitude, sincerity, serenity, and draws closer to Allah SWT. Constraints on the field were found that this sport does not yet have its own place as a sports center so that the implementation of the sport still hitched a ride in another agency, namely the Ministry of Religion and MTsN Model Padang City Keywords: nternalization, Islamic Education, and Mahatma Sports